Credit and Financial Management (Book). - Roberts, Paul C. (The Accounting Review, 1957)
Reviews the books "Credit and Financial Management," and "Credit Manual of Commercial Laws," edited by Henry H. Heimann, W. Randolph Montgomery, William C. Porth and Earnest A. Rovelstad.